Requiem for Risk: Non-knowledge and Domination in the Governance of Weapons Circulation. Issue 3 (16th December 2019) - Stavrianakis, Anna
Abstract: Analyses of risk in international political sociology and critical security studies have unpicked its operation as a preventive and preemptive political technology. This article examines the countercase of the governance of weapons circulation, in which risk has been mobilized as a permissive technology. Examining UK arms exports to Saudi Arabia and the war in Yemen, I demonstrate how risk assessment constitutes a regime of recklessness in which risk is made not to matter in three main ways: systematic not-knowing about international humanitarian law violations; claims of unintentional harm and practices of reputation management; and future-proofing the inherent temporality of risk. I argue that risk has served to facilitate arms exports despite the potential for harm: it has been mobilized as a mode of domination. This does not suggest a failure of risk as a governance strategy or a contradiction in its operation, however. Rather, it illustrates the generative character of risk as a regulatory technology in contexts marked by asymmetrical power dynamics. If the potential for domination is built into the operation of risk, we need a requiem for risk and a search for alternative grounds of repoliticization that can generate more adequate modes of regulation and accountability.